Reference and Knowledge of Reference - Gregory Bochner (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
This paper addresses two issues: (a) Does linguistic competence with respect to a given sentence S (or an utterance of S) whose meaning is that p strictly require knowledge that S means that p? (b) Of what kind is the entity which is the subject matter of the propositions embedded in the knowledge-that attributions constituting attributions of linguistic competence? These two issues are addressed in connection to some classical problems raised by names and direct reference theory. It will be argued that in order to be linguistically competent with respect to a given name it is sufficient that a speaker internalize some appropriate description of the name itself.